Synchronization of oestrus in Osmanabadi goats - PATIL, A D; KURHE, B P; PHALAK, K R; DHOBLE, R L (The Indian Journal of Animal Reproduction, 2023)
Synchronization of oestrus in Osmanabadi goats was carried out by using different hormones. The objective of the presentstudy was to evaluate mean time interval for exhibition of oestrus, duration of oestrus, conception rate and biochemical changes ofserum total protein and serum cholesterol before and after treatment and in control groups . It was observed that the efficacy of PGF2alpha for synchronization was 50 percent by IM route, 75 percent by IVSM route. The efficacy of progesterone and PMSG was 60percent. The conception rate 60.0, 66.67 and 50.0 percent in group I, II and III, respectively. Serum total protein did not showappreciable change in treatment and control groups both before and after treatment. However, the serum cholesterol level was foundto be higher after injection in treatment group between 24 to 72 hrs.
Keywords: Goat; oestrus; synchronization